Comunicação digital e educação patrimonial: análise da Revista SB Sala de Aula como recurso pedagógico na Escola Municipal Sagrado Coração de Jesus - (:unkn) unknown (Universidade Federal do Pampa, 2023)
There are many ways to preserve the history and culture of a society, one of them is valuing the people's historical and cultural heritage through a form and language in which we can also include children, as they are the ones who will continue this legacy. With that in mind, this dissertation aims to understand how the website of the SB Sala de Aula digital magazine can be a pedagogical tool in the teaching and learning of elementary school children about the history of São Borja. The research seeks a dialogue between the themes of communication, education and the Creative Industry. The methodological techniques used were bibliographic research to understand the main concepts, qualitative field research, through participant observation; semi-structured interviews with teachers and application of a questionnaire to students. Finally, we analyzed and crossed data from participant observations, interviews and questionnaires. Through this route, we arrived at some considerations that answer the guiding question of this research, Communication can contribute to the teaching of São Borjense culture and history from the Revista Digital SB Sala de Aula website because it is recognized as a pedagogical teaching tool , being able to help in the teaching of historical education in the municipality of São Borja.
Keywords: Comunicação de massa e educação; Patrimônio cultural; Periódicos eletrônicos; Ensino - Meios auxiliares; Comunicação; Ensino criativo; Cultura; Mass communication and education; Cultural heritage; CNPQ::CIENCIAS SOCIAIS APLICADAS